Partially crystallized outer layer coating for marine optical fiber and preparation method of partially crystallized outer layer coating

By using partially crystallized polyurethane acrylate prepolymer as the fiber outer coating, the crystallinity is adjusted to match the wire drawing process, the problem that existing fiber coatings cannot meet the high strength and low loss requirements of marine fibers is solved, and the excellent mechanical properties and low attenuation effect of the fiber are achieved.

CN119736013APending Publication Date: 2025-04-01YANGTZE OPTICAL FIBRE & CABLE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411912348.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing fiber outer coatings cannot meet the requirements of ultra-low loss and high strength of marine fibers, and there are few researches on the application of crystalline polyurethane in the field of marine fiber.

Method used

Partially crystallized polyurethane acrylate prepolymer is used as the fiber outer coating, and the excellent mechanical properties of the coating are achieved by adjusting the crystallinity to match the wire drawing process.

Benefits of technology

While ensuring low attenuation, the strength of the optical fiber is significantly improved and meets the high strength and weather resistance requirements of marine fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206017950000041
    Figure BDA0005206017950000041
  • Figure BDA0005206017950000051
    Figure BDA0005206017950000051
  • Figure BDA0005206017950000052
    Figure BDA0005206017950000052
Patent Text Reader

Abstract

The invention discloses a partially crystallized optical fiber outer layer coating which comprises the following components in parts by weight: 90-110 parts of a partially crystallized polyurethane acrylate prepolymer, 20-40 parts of an acrylate active monomer diluent, 1-7 parts of a photoinitiator and 0-5 parts of an auxiliary agent, the preparation method of the partially crystallized polyurethane acrylate prepolymer comprises the following steps: sequentially adding polyol, isocyanate and a catalyst into a reaction container, heating to 60 + / -2 DEG C, and carrying out heat preservation reaction for 2-2.5 hours; dropwise adding (methyl) acrylic acid hydroxyl ester and a polymerization inhibitor, and continuously reacting at 65 + / -2 DEG C for 2-3 hours until the content of isocyanate groups is zero, so as to obtain a partially crystallized polyurethane acrylate prepolymer; the partially crystallized optical fiber outer coating is excellent in mechanical property, the crystallinity can be adjusted through matching of a wire drawing process, then the mechanical property is adjusted, drawn optical fibers can obtain higher optical fiber strength while low attenuation is guaranteed, and the use requirements of ocean optical fibers are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to an outer coating for an optical fiber. Background Art

[0002] Submarine optical cables have gradually replaced coaxial cables, satellite communications, etc., and have become one of the main media for global information transmission today, due to their long transmission distance, strong anti-interference ability, high security, and good confidentiality. With the development of the global digital economy, 95% of international communication traffic is transmitted by submarine optical cables, with an annual growth rate of 30%. In recent years, global international Internet traffic has shown a sustained growth trend, and the continued growth in bandwidth demand has accelerated the construction of submarine optical cables. Currently, there are more than 400 submarine optical cables in use worldwide, with a total length of more than 1.4 million kilometers. The core of submarine optical cable communication is to achieve large-capacity communication transmission on the basis of ensuring long-term reliability. International marine communication giants regard submarine optical fiber cables as system engineering, and have formed technical barriers and market monopoly for a long time.

[0003] At the optical fiber level, due to the need for long-distance transmission, the optical fiber is required to have higher strength and lower loss, which also places higher requirements on the performance of optical fiber coatings. However, conventional optical fiber coatings on the market cannot meet the ultra-low loss and high-strength requirements of marine optical fibers.

[0004] The optical fiber outer coating in the prior art usually uses epoxy acrylate or epoxy acrylate and polyurethane acrylate as the oligomer component of the coating, but epoxy acrylate is highly brittle, has poor mechanical and thermal shock resistance, and poor weather resistance, making it difficult to match the long-term environmental use requirements of marine optical fibers; conventional photocurable polyurethane acrylate has high toughness and good weather resistance, but it is difficult to meet the high strength requirements of marine optical fibers when used alone, and research on crystalline polyurethane is mainly concentrated in the fields of polyurethane elastomers, thermoplastic polyurethanes, and polyurethane adhesives. There is no research on the application of crystalline polyurethane in the field of marine optical fibers, and these formulas and preparation processes cannot be used as optical fiber outer coatings. Crystalline polyurethane improves the strength of polyurethane, but if the crystallinity is not effectively controlled, the cured film is prone to being too brittle and insufficiently tough, which will deteriorate the strength, attenuation, and other mechanical and environmental properties of the optical fiber. Therefore, balancing the strength, toughness, and weather resistance of the coating is the key and difficulty of the outer coating for marine optical fibers. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a partially crystallized optical fiber outer coating and a curing method. The coating has excellent mechanical properties. The crystallinity is adjusted by matching the coating formula and the drawing process, and then the mechanical properties are adjusted, so that the drawn optical fiber can obtain higher optical fiber strength while ensuring low attenuation, thereby meeting the use requirements of marine optical fibers.

[0006] In order to achieve the above purpose, the technical solutions adopted are as follows:

[0007] A partially crystallized optical fiber outer coating, comprising the following components by weight:

[0008] 90-110 parts of partially crystalline polyurethane acrylate prepolymer, 20-40 parts of acrylate active monomer diluent, 1-7 parts of photoinitiator, 0-5 parts of auxiliary agent. In the optimized solution, the auxiliary agent is 1-5 parts.

[0009] The preparation method of the partially crystalline polyurethane acrylate prepolymer is as follows: polyol, isocyanate and catalyst are mixed and heated for reaction, (meth) hydroxy acrylate and polymerization inhibitor are added, and the reaction is continued until the isocyanate is completely consumed, thereby obtaining the partially crystalline polyurethane acrylate prepolymer. The structure, molecular weight and crystallinity of the self-made polyurethane acrylate prepolymer can be flexibly adjusted as needed.

[0010] According to the above scheme, the method for preparing the partially crystalline polyurethane acrylate prepolymer comprises the following steps:

[0011] (1) Add polyol, isocyanate and catalyst into a reaction vessel in sequence, raise the temperature to 60±2°C, and keep the temperature to react for 2 to 2.5 hours;

[0012] (2) adding (meth) hydroxy acrylate and polymerization inhibitor dropwise, and continuing the reaction at 65±2° C. for 2 to 3 hours until the isocyanate group content is zero, thereby obtaining a partially crystalline polyurethane acrylate prepolymer;

[0013] The raw materials used are calculated by weight: the polyol uses 80-110 parts of polycaprolactone diol, 80-100 parts of polypropylene glycol, the isocyanate uses 30-50 parts of HDI and IPDI, 25-35 parts of (meth) hydroxy acrylate, 0.1-0.4 parts of catalyst, and 0.1-0.4 parts of inhibitor.

[0014] According to the above scheme, the polyol is a mixture of polyester polyol and polyether polyol. Polycaprolactone diol is easy to crystallize and is suitable for use as the soft segment of polyurethane acrylate in the present invention, but its water resistance is poor and it is easy to cause excessive crystallinity when used alone, so it is used in combination with polypropylene glycol for performance adjustment. In order to further adjust the crystallinity and water resistance, polycaprolactone diol with a molecular weight of 1000-3000 is further preferred. The larger the molecular weight of polycaprolactone diol is, the easier it is to crystallize. Based on the commonly used wire drawing speed and other components to the contribution of crystallinity during actual production, polycaprolactone diol with a molecular weight within this range can obtain suitable crystallinity while taking into account good water resistance.

[0015] According to the above scheme, in order to be able to more flexibly regulate the crystallinity of the coating, the isocyanate selects high crystallinity isocyanate and low crystallinity isocyanate for use. As a hard segment in polyurethane acrylate, isocyanate can increase the strength of the final coating by properly improving its crystallinity, but if its crystallinity is too high, it will also lead to insufficient toughness of the cured coating and affect the optical fiber performance. Therefore, the present invention selects high crystallinity hexamethylene diisocyanate (HDI) and low crystallinity isophorone diacrylate (IPDI) for compound use, and the final crystallinity is controlled by reasonably regulating the ratio of the two.

[0016] According to the above scheme, the hydroxy (meth)acrylate is used for end-capping, and is specifically selected from one or a mixture of two or more of hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, dipentaerythritol monohydroxypenta (meth)acrylate, 2-hydroxyoctyl (meth)acrylate, pentaerythritol tri (meth)acrylate, glycerol di (meth)acrylate, 4-hydroxycyclohexyl (meth)acrylate, trimethylolpropane di (meth)acrylate, and trimethylolethane di (meth)acrylate.

[0017] According to the above scheme, the catalyst is one or a mixture of two or more of dibutyltin dilaurate, bismuth carboxylate, bismuth isooctanoate, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, N,N,N',N'-tetramethylalkylenediamine, triethylamine, N,N-dimethylbenzylamine, solid amine, N-ethylmorpholine, N,N'-diethylpiperazine, triethanolamine, dimethylaminoethanol, pyridine, and N,N'-lutidine; and the amount used is 0.1wt% to 1wt% of the total mass of the reactants.

[0018] According to the above scheme, the polymerization inhibitor is one of hydroquinone and p-hydroxyanisole; the dosage is 0.1wt% to 1wt% of the total mass of the reactants.

[0019] According to the above scheme, the acrylate reactive monomer diluent is any one of tripropylene glycol diacrylate, tripropylene glycol dimethacrylate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, tricyclodecane dimethanol diacrylate, hexadecane diol diacrylate, ethylene glycol dimethacrylate, isobornyl acrylate, isobornyl methacrylate, cyclohexyl methacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, trimethylolpropane trimethacrylate, ethoxylated trihydroxypropane trimethacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol triacrylate, and ditrimethylolpropane tetraacrylate, or a mixture thereof.

[0020] According to the above scheme, the photoinitiator is one or a mixture of two or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl benzophenone, benzoin dimethyl ether, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone.

[0021] According to the above scheme, the auxiliary agent includes any one of a defoamer, a leveling agent, an antioxidant, and a stabilizer, or any mixture thereof.

[0022] The above-mentioned (meth) hydroxy acrylate, catalyst, polymerization inhibitor, acrylate active monomer diluent, photoinitiator and auxiliary agent are all conventional raw materials, and the specific types can be reasonably selected based on their objective properties.

[0023] A method for preparing a partially crystallized optical fiber outer coating comprises preparing an optical fiber surface coating simultaneously in an optical fiber drawing process; the surface coating adopts the above-mentioned partially crystallized optical fiber outer coating; in the optical fiber drawing process, the drawing speed is 500-2000m / min, the curing temperature is 35-55°C, and the power of the ultraviolet curing lamp is 300-700W.

[0024] The crystallinity of the partially crystallized optical fiber outer coating after final curing in the present invention can also be adjusted by the curing conditions during the optical fiber drawing process to obtain the optimal optical fiber performance. 500-2000m / min is a relatively common drawing speed in the actual production of optical fibers. If it is lower than 500, the efficiency is too low, and if it is higher than 2000, it is difficult to ensure the quality. The coating formula of the present application can match the currently commonly used drawing speed, and make corresponding adjustments according to the changes in the specific drawing speed, thereby ensuring the optical fiber production efficiency while improving the performance of the optical fiber.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) Since the preparation method of the outer coating of the optical fiber is to apply the outer coating while drawing, the drawing process has an orientation effect on the coating, which can improve the crystallinity of the coating, and improving the crystallinity of the polyurethane can improve the strength. Therefore, the applicant creatively uses partially crystallized polyurethane acrylate coating to prepare the outer coating of the optical fiber. Based on the contribution of the commonly used drawing speed to the crystallinity in actual production, the component ratio is reasonably set. The crystallinity of the outer coating is jointly adjusted by the drawing process and the coating formula, and good strength and flexibility are obtained at the same time, ensuring production efficiency. While taking into account the low attenuation and excellent environmental performance of the optical fiber, the strength of the optical fiber is significantly improved, ensuring the long-distance transmission of the marine optical fiber on the seabed.

[0027] (2) In terms of components and ratios, PCL and PPG were selected as polyols based on water resistance and crystallinity, and the molecular weight of PCL was further optimized to further improve the tensile strength of the optical fiber. In order to further regulate the crystallinity, the isocyanate was selected as a compound of HDI and IPDI in a certain ratio.

[0028] (3) The present invention uses partially crystalline polyurethane acrylate as the oligomer component of the outer coating of marine optical fiber. While retaining the original excellent properties of the polyurethane material, the strength of the polyurethane is improved by introducing crystalline segments to meet the high strength requirements of marine optical fiber. The polyurethane acrylate material can adjust the crystallinity and thus the mechanical properties by changing the types and proportions of raw materials. Specifically, the soft segment of the polyurethane acrylate selects polycaprolactone diol with a molecular weight of 1000-3000 and polypropylene glycol to obtain a suitable crystallinity and good water resistance; the hard segment selects high crystallinity hexamethylene diisocyanate (HDI) and low crystallinity isophorone diacrylate (IPDI) to obtain a suitable crystallinity. In addition, the stretching induction of the optical fiber drawing process will also affect the crystallinity of the coating, which can further adjust the optical fiber performance. The appropriate drawing process is: drawing speed 500-2000m / min, curing temperature 35-55℃, UV curing lamp power 300-700W. DETAILED DESCRIPTION

[0029] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0030] A specific embodiment provides a method for preparing a partially crystalline polyurethane acrylate prepolymer, comprising the following steps:

[0031] (1) Add polyol, isocyanate and catalyst into a reaction vessel in sequence, raise the temperature to 60±2°C, and keep the temperature to react for 2 to 2.5 hours;

[0032] (2) Add (meth) hydroxy acrylate and polymerization inhibitor dropwise, and continue the reaction at 65±2°C for 2-3 hours until the isocyanate group content is zero, thereby obtaining a partially crystalline polyurethane acrylate prepolymer. The specific raw materials and amounts are shown in Table 1.

[0033] Table 1 (unit, g)

[0034]

[0035]

[0036] 100 g of the partially crystallized polyurethane acrylate prepolymer product obtained in the above Examples 1-6 were mixed with 30 g of tripropylene glycol diacrylate, TPO (2,4,6-trimethylbenzoyl-diphenylphosphine oxide) (1.95 g), 184 (1-hydroxycyclohexyl phenyl ketone) (1.95 g), and DAROCURE 1173 (2-hydroxy-2-methyl-1-phenyl-1-propanone) (1.3 g) to obtain an optical fiber outer coating, which was used in the optical fiber drawing process to simultaneously prepare a surface coating. The curing temperature was 45° C. and the power of the ultraviolet curing lamp was 500 W. The properties of the obtained optical fiber and coating are shown in Table 2.

[0037] Table 2

[0038]

[0039] Comparative Example 1

[0040] Example 1 was repeated, except that 100 g of polycaprolactone diol (2000) was replaced by 50 g of polycaprolactone diol (1000), and the rest remained unchanged.

[0041] Comparative Example 2

[0042] Example 1 was repeated, except that 100 g of polycaprolactone diol (2000) was replaced by 150 g of polycaprolactone diol (3000), and the rest remained unchanged.

[0043] Comparative Example 3

[0044] Example 1 was repeated, except that 100 g of polycaprolactone diol (2000) and 80 g of polypropylene glycol (1000) were replaced by 260 g of polycaprolactone diol (2000), and the rest remained unchanged.

[0045] Comparative Example 4

[0046] Example 1 was repeated, except that 30.24 g HDI and 17.76 g IPDI were replaced by 43.68 g HDI, and the rest remained unchanged.

[0047] Comparative Example 5

[0048] Example 1 was repeated, except that 30.24 g HDI and 17.76 g IPDI were replaced by 57.72 g HDI, and the rest remained unchanged.

[0049] Comparative Example 6

[0050] Example 1 was repeated, with the wire drawing speed being 2300 m / min and the rest remaining unchanged.

[0051] Comparative Example 7

[0052] Example 1 was repeated, with the wire drawing speed being 300 m / min and the rest remaining unchanged.

[0053] Comparative Examples 1-7 obtained optical fiber outer coatings, which were used in the optical fiber drawing process to simultaneously prepare the surface coating. The properties of the obtained optical fiber and coating are shown in Table 3.

[0054] Table 3

[0055]

[0056] As can be seen from the examples, the present application obtains a marine optical fiber outer coating formula that matches the drawing speed through specific raw material selection and ratio, obtains a suitable crystallinity, and thus achieves good strength, flexibility, water resistance and low attenuation. Example 1 has the best performance, and Examples 2-6 also have good comprehensive performance. By comparison, it can be seen that Examples 1 and 2 are used to draw optical fibers at speeds of 1000m / min and 2000m / min, respectively. Both can achieve high optical fiber strength while taking into account low attenuation and good water resistance of the optical fiber, indicating that the formula can be well adapted to the commonly used drawing speed range of 1000-2000m / min. In Examples 3 and 4, the PCL2000 in Example 1 is replaced with a compound of PCL1000 and PCL3000. The tensile strength of the cured coating film after compounding increases with the increase in the proportion of PCL3000. However, the tensile strength of the optical fibers drawn by the two is reduced compared with that in Example 1. The water resistance and attenuation of Examples 3 and 4 are not better than those in Example 1, indicating that the use of a compound of PCL1000 and PCL3000 cannot fully achieve the technical effect of PCL2000, and Example 1 is the optimal technical solution. Compared with Example 1, Example 5 changes the ratio of PCL2000 to PPG1000. After the proportion of PCL2000 decreases, the strength of the cured coating film and the strength of the drawn optical fiber both decrease. Compared with Example 1, Example 6 changes the ratio of HDI and IPDI. HDI can improve the crystallinity, and reasonable control of its proportion can further improve the strength of the cured coating film and the tensile strength of the drawn optical fiber.

[0057] In Comparative Example 1, only PCL1000 is used as polyester polyol. Since the molecular weight of the obtained crystalline polyurethane soft segment is low, it cannot be effectively arranged to form crystals, resulting in low crystallinity of the coating and low optical fiber strength. In Comparative Example 2, only PCL3000 is used as polyester polyol. After curing, the coating has high crystallinity and is too brittle, resulting in decreased optical fiber strength and increased attenuation. In Comparative Example 3, only polyester polyol PCL2000 is used without polyether polyol PPG1000. The coating has high crystallinity and insufficient toughness, resulting in decreased optical fiber strength and increased attenuation. In addition, since only polyester polyol is used, The coating formula has poor water resistance, and the additional attenuation of the optical fiber increases after being immersed in water; in Comparative Example 4, the isocyanate only uses HDI, the resulting polyurethane hard segment crystallinity is too high, and the coating is too brittle, resulting in a decrease in optical fiber strength and increased attenuation; in Comparative Example 5, the isocyanate only uses IPDI, and the resulting polyurethane hard segment crystallinity is low, resulting in insufficient optical fiber strength; in Comparative Example 6, the drawing speed is 2300, the coating is over-crystallized, and the optical fiber strength and water resistance are greatly reduced; in Comparative Example 7, the drawing speed is 300, the production efficiency is low, and the optical fiber strength is reduced, the attenuation is large, and the water resistance is poor due to the decrease in crystallinity.

Claims

1. A partially crystallized optical fiber outer coating, characterized in that The composition includes by weight: 90-110 parts of partially crystalline polyurethane acrylate prepolymer, 20-40 parts of acrylate active monomer diluent, 1-7 parts of photoinitiator, 0-5 parts of auxiliary agent; The raw materials of the partially crystalline polyurethane acrylate prepolymer include, by weight: 80-110 parts of polycaprolactone diol, 80-100 parts of polypropylene glycol, 30-50 parts in total of HDI and IPDI, 25-35 parts of (meth) hydroxy acrylate, 0.1-0.4 parts of catalyst, and 0.1-0.4 parts of polymerization inhibitor.

2. The partially crystallized optical fiber outer coating as claimed in claim 1, characterized in that: The mass ratio of HDI:IPDI is 1:(0.5-1.4).

3. The partially crystallized optical fiber outer coating as claimed in claim 1, characterized in that: The molecular weight of the polycaprolactone diol is 1000-3000.

4. The partially crystallized optical fiber outer coating as claimed in claim 3, characterized in that: The ratio of polycaprolactone diol with a molecular weight of 1000 to polycaprolactone diol with a molecular weight of 3000 is (1-9):(1-9).

5. The partially crystallized optical fiber outer coating as claimed in claim 1, characterized in that: The molecular weight of the polycaprolactone diol is 2000.

6. The partially crystallized optical fiber outer coating as claimed in claim 1, characterized in that The hydroxy (meth)acrylate is one or a mixture of two or more of hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, dipentaerythritol monohydroxypenta (meth)acrylate, 2-hydroxyoctyl (meth)acrylate, pentaerythritol tri (meth)acrylate, glycerol di (meth)acrylate, 4-hydroxycyclohexyl (meth)acrylate, trimethylolpropane di (meth)acrylate and trimethylolethane di (meth)acrylate.

7. The partially crystallized optical fiber outer coating as claimed in claim 1, characterized in that The catalyst is one or a mixture of two or more of dibutyltin dilaurate, bismuth carboxylate, bismuth isooctanoate, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, N,N,N',N'-tetramethylalkylenediamine, triethylamine, N,N-dimethylbenzylamine, solid amine, N-ethylmorpholine, N,N'-diethylpiperazine, triethanolamine, dimethylaminoethanol, pyridine, and N,N'-lutidine; and the amount used is 0.1wt% to 1wt% of the total mass of the reactants.

8. The partially crystallized optical fiber outer coating as claimed in claim 1, characterized in that: The polymerization inhibitor is one of hydroquinone and p-hydroxyanisole; the dosage is 0.1wt% to 1wt% of the total weight of the polyol, isocyanate and (meth) hydroxy acrylate.

9. The partially crystallized optical fiber outer coating as claimed in claim 1, characterized in that: The acrylate reactive monomer diluent is any one of tripropylene glycol diacrylate, tripropylene glycol dimethacrylate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, tricyclodecane dimethanol diacrylate, hexadecane diol diacrylate, ethylene glycol dimethacrylate, isobornyl acrylate, isobornyl methacrylate, cyclohexyl methacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, trimethylolpropane trimethacrylate, ethoxylated trihydroxypropane trimethacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol triacrylate, and ditrimethylolpropane tetraacrylate, or a mixture thereof.

10. The partially crystallized optical fiber outer coating as claimed in claim 1, characterized in that The photoinitiator is one or a mixture of two or more of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-hydroxy-2-methyl-1-phenylacetone, 1-hydroxycyclohexyl benzophenone, benzoin dimethyl ether, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone.

11. The partially crystallized optical fiber outer coating as claimed in claim 1, characterized in that The auxiliary agent includes any one of a defoamer, a leveling agent, an antioxidant, and a stabilizer or any mixture thereof.

12. A method for preparing a partially crystallized optical fiber outer coating, comprising: simultaneously preparing an optical fiber surface coating during an optical fiber drawing process; the surface coating adopts the partially crystallized optical fiber outer coating according to claim 1; the drawing speed in the optical fiber drawing process is 500-2000 m / min, the curing temperature is 35-55°C, and the power of the ultraviolet curing lamp is 300-700W.

13. The method for preparing the outer coating of a partially crystallized optical fiber according to claim 12, characterized in that: The preparation method of the partially crystalline polyurethane acrylate prepolymer comprises the following steps: (1) Add polyol, isocyanate and catalyst into a reaction vessel in sequence, raise the temperature to 60±2°C, and keep the temperature to react for 2 to 2.5 hours; (2) Add (meth) hydroxy acrylate and polymerization inhibitor dropwise, and continue the reaction at 65±2° C. for 2 to 3 hours until the isocyanate content is zero, thereby obtaining a partially crystalline polyurethane acrylate prepolymer.